Array pattern optimization using electromagnetism-like algorithm - Jhang, Jhen-Yan; Lee, Kun-Chou (International journal of electronics and communications, 2009)
This paper proposes a design method of array pattern optimization for sidelobe level (SLL) reduction. The element positions and their weights are determined by electromagnetism-like (EM)-like algorithm. Simulation results show that the EM-like algorithm is efficient in SLL reduction for beamwidth restriction. Synthesis of array pattern using EM-like algorithm is very straightforward and efficient. It does not require any gradient operation and is very easy in both formulation and programming. Therefore, the EM-like algorithm can be applied to many other applications in array signal processing.